Penerapan Algortima C4.5 Untuk Penentuan Kelayakan Kredit - Siti Nur Khasanah (Jurnal Techno Nusa Mandiri, 2017)
Bad credit is one of the credit risk faced by the financial industry. Bad credit happens if in the long term, financial institutions can not attract loans within the stipulated time. Credit scorings can be used to assist in determining the feasibility analysis of the credit applicant. With proper credit scoring models, banks can evaluate whether an applicant is eligible to get credit or not. In this study, carried out the classification of the customers who are categorize as good customers and bad customers by algorithm C4.5. The test results obtained for the accuracy value of C4.5 88.52%.